Preparation of a highly water-selective membrane for dehydration of acetone by incorporating potassium montmorillonite to construct ionized water channel. (2nd October 2015) - Gao, Chengyun; Zhang, Minhua; Jiang, Zhongyi; Liao, Jiayou; Xie, Xianmei; Huang, Tinghong; Zhao, Jing; Bai, Jinshuan; Pan, Fusheng
Abstract: Novel polymer–inorganic hybrid membrane was prepared by incorporating potassium montmorillonite (K + MMT) into chitosan (CS) for the dehydration of water–acetone mixture. The morphology, chemical and physical structure, as well as the hydrophilicity were characterized. The results showed that MMT uniformly dispersed in the chitosan matrix, formed hydrogen bonds with chitosan, and enhanced the thermal stability of the film. The membrane doped with 10 wt% of K + MMT exhibited the highest performance with separation factor of 2200, which was almost 8 times higher than 249 of pristine CS membrane at 50 °C for 5 wt% of water in the feed. The results suggested that the ionized water channel constructed by MMT intergallery in the hybrid membrane could greatly enhance the separation factor of CS membrane. Moreover, a plausible model for water transportation in the CS-K + MMT hybrid membranes was proposed. The results proved that K + MMT had a potential prospect in application for pervaporation. Highlights: Chitosan–potassium montmorillonite hybrid membrane was prepared. Ionic water channel was constructed by incorporated potassium montmorillonite. The hybrid membrane showed high separation factor. The possible transport mechanism for water in membrane has been proposed.